If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -2 = 3y Reorder the terms: -2 + 2y = 3y Solving -2 + 2y = 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -2 + 2y + -3y = 3y + -3y Combine like terms: 2y + -3y = -1y -2 + -1y = 3y + -3y Combine like terms: 3y + -3y = 0 -2 + -1y = 0 Add '2' to each side of the equation. -2 + 2 + -1y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1y = 0 + 2 -1y = 0 + 2 Combine like terms: 0 + 2 = 2 -1y = 2 Divide each side by '-1'. y = -2 Simplifying y = -2
| 2b(a+2)-a(3-b)+2(a+b-1)= | | 5v^2+4=5 | | N+6=-2 | | 9-18-5= | | -5(3x-8)+6x=131 | | -4*-4-5*-4+2= | | -5(v+2)+3v+7=8v+10 | | 6k-(2k-4)= | | 5(2-x)=2x+7-7x+3 | | 6-7j=-2j+3 | | 4-3t=2t-20 | | 45x+9x=0 | | 43=7+y | | -4(4y-4)-y=-4(y-3) | | 7x^4-33x+26=0 | | 18(2-3)-2x=2x | | 6x+6=3(x+9) | | 2n+9=15 | | 4n+1=-23-2n | | g(x)=-f(-4) | | 3x-2y=-7 | | 6-7j=2j+3 | | 25W^2+10W+1=0 | | 5x+9=2(2x+3) | | -5x(4x-8y+4)= | | 3u+45=9(u+9) | | 2x^2+14x-144=0 | | -3x+5+6(x+1)=-2+3 | | 2(x+2)+4x=x+6 | | 9+c=-13 | | 4(s+2)-s=3(s+1) | | t=4n+4v |